Thermal diffusivity of few-layers graphene measured by an all-optical method. (7th October 2015) - Cabrera, H; Mendoza, D; Benítez, J L; Bautista Flores, C; Alvarado, S; Marín, E
Abstract: We report on the measurement of the thermal diffusivity, D, of few-layers graphene obtained by chemical vapor deposition, using a noncontact optical microscopy method based on a mode mismatched thermal lens technique in a pump-probe two-laser beams configuration. It takes advantage of the coaxial counter propagating tightly focused excitation and collimated probe beams in an improved thermal lens microscopy setup. The obtained results: D   =  (6.5  ±  0.09)  ×  10 −4 m 2 s −1, D   =  (1.9  ±  0.07)  ×  10 −4 m 2 s −1 and D   =  (1.3  ±  0.05)  ×  10 −4 m 2 s −1 for four (on a glass slide), eight and sixteen graphene (freestanding) layers are reasonable values, as can be concluded from reported literature data.